2021
DOI: 10.1111/jfpp.15807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pretreatment and drying methods on the quality and stability of dried sweet potato slices during storage

Abstract: Effects of blanching, osmotic dehydration, and/or ultrasound combined with hot air (HAD), microwave vacuum (MVD), and freeze drying (FD) on the stability of quality attributes of sweet potatoes during 90 days of storage at room temperature were investigated. Pretreated sample prior to two-step drying (HAD-MVD) preserved sweet potato color better compared to unblanched and FD samples during storage. X-ray How to cite this article:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The lower color change by applying ultrasound treatment was also reported from Lagnika et al (2021). The higher a value of FD-dried raspberry compared to hot air-dried samples was also reported from Bustos et al (2018).…”
Section: Color and Surface Characteristicsmentioning
confidence: 58%
“…The lower color change by applying ultrasound treatment was also reported from Lagnika et al (2021). The higher a value of FD-dried raspberry compared to hot air-dried samples was also reported from Bustos et al (2018).…”
Section: Color and Surface Characteristicsmentioning
confidence: 58%
“…As well as being more stable during storage, dried processed foods can be healthy and nutritious if prepared with the appropriate technologies [ 104 ]. Pretreatments before drying and processing can avoid nutrient losses and change the physical and chemical characteristics of the final products, even improving the nutritional value of the sweet potato.…”
Section: Effect Of Sweet-potato Processing On Phenolic Compoundsmentioning
confidence: 99%
“…Pretreatments before drying and processing can avoid nutrient losses and change the physical and chemical characteristics of the final products, even improving the nutritional value of the sweet potato. Ultrasound (US) [ 104 ] and vacuum impregnation (VI) [ 105 , 106 ] are the most frequently applied pretreatments for sweet potatoes.…”
Section: Effect Of Sweet-potato Processing On Phenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phahom et al (2021) reported that the monolayer moisture content of commercial crab stick in France ranged from 3.65 to 5.36% d.b. Drying is one of the water removal techniques used for lowering water activity in foods and it can be performed by several methods including hot air drying, heat pump dehumidified drying, microwave drying, and freeze drying (Lagnika et al, 2021; Phahom et al, 2017, 2021; Phahom & Phoungchandang, 2018; Wahengbam et al, 2020). The freeze drying is considered as one of the most effective drying methods as it is performed under low temperature and pressure, resulting in a high product quality with high nutrients and active ingredients retention (Jiang et al, 2014; Phan et al, 2021; Silva‐Espinoza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%